Analisis Faktor-Faktor Yang Mempengaruhi Luas Pengungkapan Sukarela Laporan Keuangan Tahunan - M. Khoirul Mubarok; Khanifah khanifah; Atieq Amjadallah Alfi (AKSES: Jurnal Ekonomi dan Bisnis, 2015)
This study aims to analyze the factors of voluntary disclosure of annual financial statementsin manufacturing companies listed on the stock exchange Indonesia period 2010-2013.Factors affecting voluntary disclosure are represented by six independent variables andvoluntary disclosure being the dependent variable. Data from this study were obtained fromannual reports of manufacturing firms taken from Indonesia Stock Exchange and IndonesiaCapital Market Directory. The population of this study are manufacturing companies listedon the Indonesia Stock Exchange during 2010-2013 as many as 152 companies that issuedannual reports in a row. Determination of sample using purposive sampling method. The typeof data used is secondary data with media in the form of financial statements ofmanufacturing companies. Data analysis tool used is multiple regression analysis (multipleregression). The result of this research shows that profitability ratio, leverage ratio andrentability ratio do not positively influence, while size with significance value 0.050, publicshare ownership with significance value 0.008 and managerial share ownership withsignificance value 0.013 have positive and significant influence to the completeness of thevoluntary disclosure in the company's annual report.Keywords: profitability, leverage, rentability, size, public share ownership, managerialshare ownership.